Outcomes of Operatively Managed Lumbar and Sacral Facet Fractures in Pediatric Athletes: A Case Series. Issue 1 (4th January 2022) - Nazareth, Alexander; Andras, Lindsay M.; Illingworth, Kenneth D.; Miller, Daniel J.; Cahill, Patrick J.; Skaggs, David L.
Abstract : Background: Facet fractures have been reported in a total of 6 young athletes in 4 previous publications. These injuries were not diagnosed on magnetic resonance imaging (MRI) or radiographs, and were identified on computed tomography (CT). Our purpose was to report a series of athletes with operatively managed facet fractures. This may be an under-recognized diagnosis. Methods: Retrospective review of pediatric patients with operatively managed isolated lumbar or sacral facet fractures from 3 tertiary pediatric hospitals from 2014 to 2019. Clinical records and imaging studies were reviewed. Results: Ten patients with symptomatic lumbar or sacral facet fractures met inclusion criteria (mean age at presentation; 13.3±2.1 years, 70% Female). All patients reported competitive participation in sports. On physical examination, 10/10 (100%) of patients had lower back pain that was exacerbated with lumbar spine extension. Limited CT scans demonstrated facet fractures in 10/10 (100%) patients not detected on plain film or MRI. All patients experienced significant relief of pain following excision of the facet fracture fragment. At time of first postoperative visit, 9/10 (90%) patients were pain free while one had generalized back pain thought to be related to fibromyalgia and not facet pathology. At time of last follow-up, 2/10 (20%) of patients reported nonspecific back pain that was not localized in the area of the facet fracture, while 80% (8/10) remained pain free. All patients 100% (10/10) returned to full participation to sports. There were no complications noted in this series. Average follow-up was 27 months (range: 1 to 68 mo). Conclusions: Athletes with localized back pain exacerbated by spine extension may have a facet fracture. As facet fractures are usually not identified with radiographs or MRI, a limited CT scan should be considered in the evaluation of pediatric athletes with localized back pain exacerbated by extension. In this series, surgical excision of facet fracture fragments was safe and provided predictable pain relief.